Search for Origins: The Prelude and Confessions - Domines Veliki, Martina (Array, 2008)
Both works, William Wordsworth’ s The Prelude and Jean-Jacques Rousseau’ s Confessions, place great confidence in the workings of memory and the vocabulary of ‘ thought and feeling’ combined together. Both writers seek the point of origin in their childhood. The child feels the unity of his mind and heart with the objects of Nature and, at first sight, it looks as though Nature is there as that stable point of origin, the unifying force in the process of child’ s developing consciousness. Yet, the possibility of finding Romantic origins seems to be a paradoxical pursuit. Each childhood ‘ spot of time’ evades fixation the moment the feeling of guilt creeps in. This feeling points beyond the mimetic reading of such scenes as they become supersaturated with significance. In other words, each ‘ spot of time’ becomes a new ‘ place’ to be revisited, a new scar cut deeply into the writer’ s ‘ present’ identity. The Romantic claim to “ exemplary self-knowledge” , to use de Man’ s words, is a fallacy because it is entrusted to written language. Yet, it is a necessary fallacy because the movement from the childhood acts of transgression to the writer’ s ‘ present’ self requires re-creation, re-writing and therefore re- reading.